Patterns of European youngsters’ daily use of media - Pacheco, Liliana (2017)
The mediatisation of young people daily lives constitutes a significant subject due to the expressive use of media in their daily routines. In this article, we resort to a representative sample of 3609 online respondents aged between 14 and 30 years old from nine European countries (Belgium, Croatia, Denmark, Germany, Hungary, Israel, Italy, Poland and Portugal), in order to perceive the impact new (and “old”) media have in these youngsters daily media consumption activities. The results of this online survey show complementary uses between networked and traditional media, but also highlight a gradual substitution of “old” by “new” networked individualized media when leisure and news-related activities are at stake.